Impact of Seasonal Variations on Bacterial, Yeast and Mold’s Count in Drinking Water Collected from Karachi Pakistan - Urooj, Shaista; Mirani, Zulfiqar Ali; Naz, Shugufta (PSM Microbiology, 2018)
The present study was conducted to assess the microbiological quality of drinking water collected from different areas of Karachi, Pakistan, during 2014 to 2015. A total of 320 samples were analyzed; of those 120 were bottled water and 200 samples were collected from the municipal water supply (Tap water). Most probable number (MPN) technique in MacConkey’s broth was used for the analysis of coliforms and fecal-coliforms and membrane filtration technique on Dichloran Rose-Bengal Chloramphenicol Agar (DRBC) was used for yeast and mold analysis. All of the bottle samples were free of coliforms and fecal-coliforms but tap drinking water samples were highly contaminated with total bacterial load, coliforms and fecal coliforms. It has been observed that bacterial as well as yeast and mold’s count was high in all of the water samples during summer. To overcome high risk of water-borne diseases, provision of improving water quality and adaptation of wash practices considered to be a part of monitoring framework system and a strict code of conduct should be implemented.